Energy storage system control strategies for power distribution systems - Kajorndech, Areewan; Rerkpreedapong, Dulpichet (Engineering and Applied Science Research, 2015)
Energy storage systems have been widely employed to attain several benef its, such as reliability improvement, stabilization of power systems connected with renewable energy resources, economic benef its and etc. To achieve the above objectives, the appropriate and effective control strategies for energy storage systems are needed to be developed. This research proposes energy storage system control strategies for power distribution systems equipped with a limited size of energy storage system in order to improve reliability and save energy costs by determining an optimal charging schedule of the energy storage system. Simulation results demonstrate the benef its of energy storage system applications under the different control strategies.